Long-Term Neurophysiologic Impact of Childhood Sleep Disordered Breathing on Neurocognitive Performance - Quan, Stuart F. (2013)
STUDY OBJECTIVE: To determine the impact of sleep disordered breathing (SDB) in children on neurocognitive function 5 years later. DESIGN, SETTING, AND PARTICIPANTS: A subgroup of 43 children from the Tucson Children’s Assessment of Sleep Apnea Study (TuCASA) who had SDB (RDI ≥ 6 events/hour) at their initial exam (ages 6–11 years) were matched on the basis of age (within 1 year), gender and ethnicity (Anglo/Hispanic) to 43 children without SDB (Control, RDI ≤ 4 events/hour). The Sustained Working Memory Task (SWMT) which combines tests of working memory (1-Back Task), reaction time (Simple Reaction Time) and attention (Multiplexing Task) with concurrent electroencephalographic monitoring was administered approximately 5 years later. RESULTS: There were no differences in performance on the working memory, reaction time and attention tests between the SDB and Control groups. However, the SDB group exhibited lower P300 evoked potential amplitudes during the Simple Reaction Time and Multiplexing Tasks. Additionally, peak alpha power during the Multiplexing Task was lower in the SDB Group with a similar trend in the Simple Reaction Time Task (p=0.08). CONCLUSIONS: SDB in children may cause subtle long-term changes in executive function that are not detectable with conventional neurocognitive testing and are only evident during neuroelectrophysiologic monitoring.